2021
DOI: 10.3390/ijerph18115914
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Self and External Regulation of Learning in Higher Education Students in Brazil

Abstract: The satisfaction of university students with the variables that regulate their learning provides very valuable information to improve the quality of teaching processes. The main objective of this study was to evaluate the learning of Brazilian university students, exploring both self-regulation variables, such as study techniques; and more external regulation variables, namely, satisfaction with the teaching–learning process and with the infrastructure, based on three variables: gender, the institution of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
1
0
0
Order By: Relevance
“…These results point to something that other studies on teaching and learning have already shown: personalised education is one of the best tools for favouring student learning and retention[ [52] , [53] , [54] ]. In this case, it is identified as the main dimension for helping students finish their degree and preventing those who feel inclined to drop out from doing so.…”
Section: Discussionsupporting
confidence: 65%
“…These results point to something that other studies on teaching and learning have already shown: personalised education is one of the best tools for favouring student learning and retention[ [52] , [53] , [54] ]. In this case, it is identified as the main dimension for helping students finish their degree and preventing those who feel inclined to drop out from doing so.…”
Section: Discussionsupporting
confidence: 65%